I DO NOT LOVE YOU ANYMORE: WHAT DO WE DO TO THE DOG? - Lança, Hugo Cunha (2020)
Animals have a new centrality in social life, and the Law is not immune to the coming of society. At a time when love for animals seems unconditional, but marriage is a term, it is important to assess the fate of the pet in case of divorce. The research methodology used is based on the combination of three theoretical and methodological axes, based on (i) dogmatic research, with regard to the use of doctrine, jurisprudence and current legislation, (ii) in socio-legal research, seeking to identify and analyze the inconsistencies of the legal system by relating it to other sciences such as sociology and psychology, inter alia, and in epistemological research, based on the study of the legal system as a whole and of the legal norms and the jusphilosophical concepts that compose it. With this text, we intend to test solutions to the problem, offering guidelines for the law enforcer, using the reality and Portuguese legislation as a paradigm.